Intelligent technologies for Web-based control systems - Mnushka, O. V. (My University, 2019)
In the paper, the mobile automotive telematics system (MATS) for testing and development purposes proposed. MTAS is based on a single-board computer (SBC) and using a sensor network for data acquisition. For flexibility two various data protocols used – on for field devices, another – for data exchange between units of systems. The system use intelligent web-based SCADA solutions for data acquisition and processing. The hardware prototype of the system to run the main software modules has been proposed and discussed.
Keywords: Internet of Things; SCADA; single-board compute; telematics